PENGARUH PENGGUNAAN BAHAN AJAR BERBASIS AUDIO VISUAL TERHADAP KECERDASAN BERBAHASA ANAK USIA 5-6 TAHUN DI PAUD MAWAR, BANJARSARI - Ernasari, Siti; Hidayati, Leni; Hidayat, Yusuf (Jurnal Intisabi, 2025)
Stimulation of language intelligence in early childhood aged 5-6 years is an important part of the development in pre-school education. This study aims to determine the effect of using audio visual-based teaching material on early childhood’s aged 5-6 years language intelligence. The method used in this study is a quantitative with a pre-experimental design. The results of the study showed that early childhood’s aged 5-6 years language intelligence at PAUD Mawar experienced a difference between before being given treatment and after being given treatment using audio-visual-based teaching material. Furthermore, based on the results of the t-test, it was obtained that the t-count > table was obtained, which was 5,046 > 2,365, so that H0 was rejected and H1 was accepted, meaning that there was an effect of using audio visual-based teaching material on early childhood’s aged 5-6 years language intelligence at PAUD Mawar. In conclusion, there is a significant effect of using audio visual-based teaching material on early childhood’s aged 5-6 years language intelligence at PAUD Mawar. Thus, this study has implication for optimizing the use of digital-based teaching media to stimulate the six aspects of early childhood development at the pre-school education level.